"The Bloody Hell and Holy Cow Moment:" Feeling Awe in the Art Museum. (8th March 2021) - Luke, Jessica J.
Abstract: Research shows that awe has various positive benefits for people. Research also suggests that viewing art can elicit awe. Therefore, art museums seem well positioned to foster awe, yet there is almost no evidence that art museum visitors experience awe during their visit. This study assessed whether and how people experience awe during an art museum visit, to establish an empirical foundation. A total of 132 adults were interviewed at two different art museums in London, UK. Study results point to three key findings: (1) art museum visitors say that they feel awe, and it may be correlated with several other positive emotions; (2) art museum visitors say that they experience some dimensions of awe more strongly than others; and (3) art museum visitors mostly felt that it was aspects of the art work that elicited their feelings of awe in the art museum. Results have implications for art museum practitioners developing interpretive strategies for connecting people with works of art, and for researchers investigating the nature of museum experiences.